EFFECT OF REPLACMENT CRUDE AND GERMINATED SORGHUM INSTEAD OF YELLOW CORN IN THE PRODUCTIVE PERFORMANCE AND SOME BIOCHEMICAL PARAMETERS OF BROILER - Duried Younis; Nawaf Kazi Abood (Mesopotamia Journal of Agriculture)
This study was conducted at Poultry Farm-Department of Animal Resources- Collage of Agriculture and Forestry University of Mosul. to identify the effect of replacement of different levels of sorghum instead of yellow corn in broiler diet and the effect of germinated of sorghum on broiler performance and some biochemical traits of blood. Four hundred twenty unsexed one day old Ross chickens were used in this study. Birds were weighted and distributed into 7 treatments (3 replicates each, 20 birds / replicate).Treatments continued for 49 days, as follows: T1: control (100 % yellow corn).T2, T4 and T6: replacement of 50, 75 and 100 % crud sorghum instead of yellow corn. T3, T5 and T7: replacement of 50 75 and 100 % germinated sorghum instead of yellow corn.The Results revealed. Significant increase (P ≤ 0.05) in Feed consumption for birds in T3, improvement in feed conversion ratio in T7, Percentage of heart, gizzard and edible viscera in birds of T4 and T6. Percentage weight of pancreas and AST enzyme level in T6 .  Albumin level in the blood of birds in control, T5 and T7. Significant decrease in Body weight of birds in T6. Total protein concentration in treatments of sorghum replacement. In general, it was concluded from this study that the possibility of replacement of 100 % germinated local sorghum instead of yellow corn in broiler diets without any negative significant effects on productive performance.